Development and Validation of the Approach-Avoidance System Questionnaire (AASQ) - Teboul, Anne; Klosek, Cyril; Montiny, Camille; Gernigon, Christophe (Frontiers in Psychology, 2019)
Gernigon et al. (2015) recently proposed a dynamical model of approach and avoidance, according to which approach and avoidance patterns are accounted for by a control parameter k, which results itself from the interactions among a limited number of key social-cognitive variables: competence expectancies (c), benefit for the self (bs), and threat for the self (ts). The present research aimed to develop and validate a French questionnaire that measures these variables, the Approach-Avoidance System Questionnaire (AASQ). A first study revealed a satisfactory three-factor structure based on 12 clear items. A second study confirmed the validity of this factorial structure and showed that k and mastery-approach goals were the only significant predictors of autonomous motivation regarding sport sciences studies, and that k was the only predictor of academic achievement in these studies. These findings support the validity of the AASQ, an instrument that now enables new types of research on approach and avoidance dynamics.